Paricipation in Bauru marter plans, Brazil: analysis of the historical evolution of the consultation process - Barbassa, Ademir Paceli [UNESP]; Rigitano, Maria Helena Carvalho [UNESP] (Consortium Erudit, 2010)
In Brazil, a policy on citizen participation and consultation in urban intervention programs, in particular in the development of master plans, was first introduced into the Federal Constitution in 1988. This article presents an historical reconstitution of Master Plans in Bauru – State of São Paulo – Brazil. The 1968, 1988 and 2005/2006 consultation methods are analyzed using established criteria. The degree of community participation in the processes is estimated by drawing on a typology based on the level of involvement by residents. The effects of participation caused by changes in political regime, technical planning vision, legal support to consultation, recognition of community importance and knowledge acquired during the process are highlighted and discussed.

La participation citoyenne est instrumentalisée au Brésil depuis 1988, date à laquelle la constitution fédérale a réglementé la participation dans les programmes d’urbanisme, plus spécifiquement dans le développement des schémas directeurs. Cet article présente une reconstitution historique des schémas directeurs développés à Bauru – Etat de Sao Paolo – Brésil. D’abord, les méthodes de consultation participative de 1968, 1988 et 2005/2006 sont comparées à l’aide d’une grille d’analyse. Ensuite, le degré de participation communautaire aux processus est estimé par l’application d’une typologie fondée sur le niveau de participation des habitants. Enfin, nous proposons de mettre en évidence et de discuter les effets produits par les changements de coalitions d’acteurs au pouvoir, de l’approche de la planification stratégique, du cadre juridique dans lequel s’inscrit la consultation participative, de la reconnaissance de l’importance de la communauté et du savoir-faire acquis au long du processus.
Keywords: Citizen participation; Participative process; Master plans; Participation citoyenne; Processus participatif; Plans directeurs